Undergraduate students' perspectives of healthcare professionals' use of shared decision-making skills. Issue 4 (4th July 2018) - Hendricks-Ferguson, Verna L.; Ruebling, Irma; Sargeant, Darina M.; Kienstra, Kathleen; Eliot, Kathrin A.; Howell, Timothy G.; Sebelski, Chris A.; Moore, Karen S.; Armstrong, Kathleen
ABSTRACT: Essential for future healthcare professionals (HCPs) to delivering ethical and empathetic patient-centred care (PCC) as a team is the understanding of appropriate shared decision-making (SDM) responses when facilitating discussions with patients and family members. The purpose of this study was to evaluate undergraduate students' perspectives about HCPs' use of SDM as described in a case-study reflection assignment. An exploratory qualitative approach was used to analyse student-reflection assignments. The sample included 42 undergraduate students enrolled in an interprofessional education (IPE) course at a Midwest university based in the United States. Data consisted of student responses in a course reflection assignment that captured their perspectives about recommended SDM responses by HCPs. Student assignments were randomly selected using stratified sampling to provide representation of eight HCP roles. Analysis revealed two themes related to students' use of SDM responses. Results provide evidence supporting the tenet that through IPE, healthcare students can develop an understanding of SDM and ethical principles related to PCC.